COMPUTER AIDED PROCESS PLANNING FOR VACCUM CLEANER BODY CASING WITH NC TOOL PATH GENERATION - Adarsh Kumar, Pranit Prakash Metkar, Annamalai k (International Journal of Research Science and Management, 2014)
CAD/CAM (Computer Aided Design / Computer Aided Manufacturing) has been utilized in different ways by different people. Some people utilize it to produce drawing and document designs, visual tool by generating shaded images and animated displays, tool path generation, and process planning tools for machining of complex product. This research includes process planning for product manufacturing, machining conditions, and setting the time standards for a product. This research eliminates the demerits of traditional production planning and also improves the quality of a design with the help of CAM tool for CNC programming. It also includes product life cycle management technique which is used for production planning.